2016
DOI: 10.4314/jasem.v19i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Speciation of Candida Species among Non-gravid young Females in Ilorin, North Central, Nigeria

Abstract: This study investigated the incidence and speciation of Candida species among non-gravid young females, using commercially available chromogenic Candida speciation media (CHROM agar) for the identification/speciation of medically important yeast and yeastlike organisms in a routine clinical mycology laboratory. High Vaginal Swabs (HVS) were randomly collected from consenting non-gravid-young females for the study. The participants also completed a structured questionnaire assessing demographic data, symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Of the 176 subjects recruited in this study, 54 were confirmed to have VVC, resulting in a prevalence rate of 30.7% among the participants. The prevalence rates we found are slightly higher than those reported by previous studies [13,16,17,19]. However, our data were more or less consistent with the frequencies reported by previous studies conducted in India (36%), Uganda (45.4%), and in the middle belt of Ghana (36.5%) [15,38,39].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Of the 176 subjects recruited in this study, 54 were confirmed to have VVC, resulting in a prevalence rate of 30.7% among the participants. The prevalence rates we found are slightly higher than those reported by previous studies [13,16,17,19]. However, our data were more or less consistent with the frequencies reported by previous studies conducted in India (36%), Uganda (45.4%), and in the middle belt of Ghana (36.5%) [15,38,39].…”
Section: Discussionsupporting
confidence: 86%
“…As a result, compared to Candida albicans, NAC are developing resistance to most antifungals used as therapy to treat VVC [16,17]. This is widely attributed to the use of over the counter (OTC) drugs and empiric regimes to treat these infections, since speciation and antifungal susceptibility testing of Candida isolates are not done routinely for clinical purposes [18,19] in Ghana. Most frequently, azole-based drugs are the drug of choice for treating Candida infections [20].…”
Section: Introductionmentioning
confidence: 99%